Kindheit, Kultur und moralische Emotionen zur Sozialisation von Furcht und Wut im ländlichen Madagaskar - Scheidecker, Gabriel 1982- (EmotionsKulturen, 2017)
How do children in a Madagascan community learn to fear their parents, to regulate their anger, and enjoy themselves with friends? A cultural-anthropological contribution to emotional research